Bilingual resources in English-medium instruction lectures - M. Angeles Velilla Sánchez (Language Value, 2021)
English is increasingly used as a lingua franca (ELF) for academic activities in Spanish higher education institutions. The notion of ELF is now being redefined including in its conceptualization a multilingual nature of communication (Jenkins, 2015). This conception is interesting for researchers in English-medium instruction (EMI). Therefore, this paper reports on a study which focuses on the multilingual resources most frequently used by higher education lecturers to achieve comprehensibility in EMI courses at the University of Zaragoza. It regards them as part of the pragmatic and strategic behaviour of the participants. The corpus for the study consists of 14 hours of audio-recorded lectures in two different disciplines that have been analysed from a discourse-pragmatic approach, involving both qualitative and quantitative methods. The analysis of the data reveals that lecturers use their multilingual resources, mainly their own first language, as a pragmatic strategy that enables them to achieve various conversational goals such as clarifying meaning.